Unearthing Campus Culture in Philippine Private Higher Education: A Case Study on Gender Mainstreaming and Policy - Rodriguez, Leal (Review of Women's Studies; Vol 29 No 1 (2019): Review of Women's Studies Volume XXIX, Number 1 (2019), 2023)
The 20th anniversary of the Beijing Platform for Action (BPfA) and the release of the Commission on Higher Education (CHED)’s Memorandum Order No. 1 (CMO-1) on gender mainstreaming sparked an assessment of gender mainstreaming's effectiveness in education. Conducted from October to December 2015, the paper is a case study on the gender culture of a school that is in the process of complying with CMO-1. This school is a private, co-educational institution of higher education (IHE) in the Philippines' National Capital Region (NCR). Key informant interviews (KIIs) with two administrators, focus group discussions (FGDs), and in-depth interviews (IDIs) of 17 student leaders and volunteers revealed the students' experiences in the campus that are related to issues of security (microaggression and sexual harassment) and equity (gender-fair language and gender stereotyping). Participants described the gender issues they faced in the absence of an explicit and overarching gender policy on campus. Notable themes include a culture that normalizes gender-based violence, the invisibilization of the lesbian, gay, bisexual, and transgender (LGBT) community, and the privileging of men in the IHE. The results of this paper were used to generate concrete policy and program recommendations in light of gender mainstreaming.